Cyclic Vomiting Syndrome in Patients Affected by Jansen–de Vries Syndrome: Results From an International Survey - Pizzol, A.; Adams, K. A.; Vries, B. B. A.; Curry, C. J.; Calvo, P. L. (American journal of medical genetics. Part A, 2025)
ABSTRACT Jansen–de Vries syndrome (JdVS) is an autosomal dominant neurodevelopmental disorder with intellectual disability and gastrointestinal (GI) abnormalities, including recurrent vomiting. This study aimed to understand the frequency and severity of GI symptoms in JdVS patients and to investigate the potential association with cyclic vomiting syndrome (CVS), which has not been previously reported. An international online survey assessed the prevalence and features of CVS and GI disorders in JdVS patients using Rome IV Criteria. The anonymous survey was conducted via Google Forms in April 2021. A total of 21 patients/guardians responded to the survey. The average age at JdVS diagnosis was 8.22 years (range: 1–42). Of the respondents, 6 (28.5%) had a CVS diagnosis, 5 (23.8%) had migraine, and 2 (9.5%) had abdominal migraine. Additionally, 8 (38%) had gastroesophageal reflux disease (GERD) and 8 (38%) had functional constipation. An analysis targeted questions showed that 7 (33%) met the Rome IV Criteria for CVS but were undiagnosed, leading to a CVS prevalence of 61% in this cohort. This study highlights a high prevalence of CVS in JdVS patients and underscores the need for increased awareness and accurate diagnosis to address misdiagnosis.